A comparative evaluation of the effect of dentin desensitizers on the retention of complete cast metal crowns - Saili M Chandavarkar; Sabita M Ram (Wolters Kluwer Medknow Publications, 2015)
Context: Desensitizers are used to reduce dentin hypersensitivity. They affect the surface texture of prepared dentin and may alter the retention of fixed restorations. Aims: The aim was to evaluate the effect of dentin desensitizers on the retention of complete cast metal crowns luted with glass ionomer cement. Subjects and Methods: Fifty freshly extracted human premolars were subjected to standardized tooth preparation (20° total convergence, 4 mm axial height) with a computer numerically controlled machine. Individual cast metal crowns were fabricated from a base metal alloy. Dentin desensitizers included none (control), a glutaraldehyde (GLU) based primer (Gluma desensitizer), casein phosphopeptide (CPP)-amorphous calcium phosphate (ACP) (GC Mousse), erbium, chromium: YSGG laser (Waterlase MD Turbo, Biolase) and Pro-Argin (Colgate Sensitive Pro-Relief desensitizing polishing paste). After desensitization, crowns were luted with glass ionomer cement and kept for 48 h at 37°C in 100% relative humidity. The samples were tested using a universal testing machine by applying a load at a crosshead speed of 0.5 mm/min. Statistical Analysis Used: Statistical analysis included One-way ANOVA, followed by the Scheffe post-hoc test with P < 0.05. Results: All dentin desensitizers showed significantly different values: Pro-Argin (4.10 Megapascals [Mpa]) < CPP-ACP (4.01 mpa) < GLU based primer (3.87 Mpa) < Virgin dentin (3.65 Mpa) < LASER (3.37 Mpa). Conclusions : On comparing the effect of prepared virgin dentin, GLU based primer, CPP-ACP, LASER and Pro-Argin on the retention of complete cast metal crowns luted with glass ionomer cement on prepared teeth, it can be concluded that Pro-Argin and CPP-ACP showed the best retention in this in vitro study.